Vascular anomaly: Cause of infant respiratory distress and dysphagia. (2019) - Baig, Aisha; Fortner, Christopher; Rivera, Marcus; Merrow, Jill; Gupta, Saurabh; Sher, Erica; Mortelliti, Anthony
Abstract: Aberrant right subclavian artery with a left aortic arch is rare, but it is the most common congenital aortic arch anomaly. It can present as an incidental finding later in life or be symptomatic at a young age. Here, we describe a case of an aberrant right subclavian artery discovered in a 4 month old with respiratory distress and feeding difficulties. She underwent an extensive aerodigestive evaluation including bronchoscopy, both flexible and rigid, upper GI endoscopy, modified barium swallow with esophageal sweep, chest imaging, CT thorax and echocardiogram. The final decision per the management team was to observe the patient in order to allow more growth. She ultimately improved with age and remains asymptomatic.